PENGEMBANGAN APLIKASI GAME PLATFORM HAPPY JUMP: WORLD ADVENTURE - Rifan Alamsyah; Sri Sulastri; Lupi Krisrupianti; Aldy Rialdy Atmadja (Jurnal Accounting Information System (AIMS), 2019)
Game is media entertainment are much sought after by today's society, including children. By using a media game players will feel how the game goes and focus in the game so that the players can feel the feeling of delight in playing it. Therefore, the author will design and build a game called Happy Jump: World Adventure with endless game genre. This game tells the story of a character named Happy to jump and collect as many coins as he is capable of with the existing obstacles. There are two worlds which can be happy play i.e. mountain and graveyard, each world has a degree of difficulty and different enemies. This game is intended for all ages. This game is built using Construct 2 in the Assembly of the components of the game and Corel Draw x6 for manufacturing assets.